Ultrasound-Guided Percutaneous Ethanol Injection Protocol to Treat Solid and Mixed Thyroid Nodules - Felício, João Soares; Conceição, Antônio Maria Silva; Santos, Flávia Marques; Sato, Michelle Masuyo Minami; Bastos, Fabíola de Arruda; Braga de Souza, Ana Carolina Contente; Koury, Camila Cavalcante; Neto, João Felício Abrahão; Cunha de Melo, Franciane Trindade; Carvalho, Carolina Tavares; Arbage, Thaís Pontes; Junior, Antonio Bentes de Figueiredo; et al. (Frontiers in Endocrinology, 2016)
Context: Ultrasound (US)-guided percutaneous ethanol injection (PEI) has been proposed for treatment of benign thyroid nodules (TNs). However, there is no consensus for the optimal amount of ethanol injection, number of applications and time to re-evaluation in order to achieve maximum volume reduction with minimum adverse effects. Objective: The purpose of the present study was to analyze the effectiveness of an US-guided PEI protocol to treat solid and mixed TNs. Patients and methods: We performed a prospective study evaluating the results of PEI in 52 patients with benign solid and mixed TNs. The ethanol dose was fixed in 30% of the nodular volume per session. Patients returned 1 month after each session for US re-evaluation. Therapeutic success was defined as volume reduction of at least 50% and/or aesthetic satisfaction reported by the patient. Results: We performed a mean of 2.8 ± 1.9 PEI sessions, with an average total volume of ethanol injected of 9.1 ± 10.3 ml, and a follow-up time of 10.0 ± 8.7 months. There was a reduction of at least 50% of the initial nodular volume in 33 patients (63.5%). In 11 patients (21.2%) the reduction did not reach 50% (mean reduction of 31 ± 11 %), but six of them reported aesthetically satisfactory results and treatment was stopped. Our therapeutic success rate considering the patients with aesthetic improvement was 75%. There were no severe complications. Conclusions: Our protocol is effective and safe to treat solid and mixed benign TNs.